An experimental investigation of shape memory polymers and its application - Yeo, Junior Zhixuan (2016)
In recent years, shape memory polymers have been extensively researched for various application purposes ranging from medical to biological applications. Two particular polymers have shown great potential in the field of research are, crosslinked poly-ethyleneglycol dimethacrylate (PEGDMA) and crosslinked Poly[ethylene-co-(vinyl acetate)] (cPEVA). PEGDMA hydrogel exhibits swelling effect under the influence of water and it also possess shape memory effect that is triggered by various stimuli. On the other hand, cPEVA also exhibits shape memory effect with the presence of heat as stimulus. The objectives of this report is to determine the relationship of crosslinked PEGDMA mechanical properties such as optical transmission properties and elongation with change in humidity, and the shape memory effect of cPEVA with addition of additives such as Dicumyl Peroxide (DCP), carbon nanoparticles and iron nanoparticles. In this report, PEGDMA is crosslinked with 2-hydroxy-2-methylproppiophenone photo-initiated crosslinker, and deionized water. Mechanical properties of PEGDMA are then tested in a humidity chamber with temperature set at a constant of 30˚C. cPEVA with DCP, carbon nanoparticles and iron nanoparticles are prepared by compounding the mixture with an extruder at 110˚C. Programming of the samples is done with an Instron tensile machine and the mechanical properties are tested with Dynamic Mechanical Analysis (DMA). cPEVA with 0.5% Iron nanoparticles additive was able to retain its shape memory effect.